Development of Monitoring Clinical Learning (MCL) Application on the Competency Achievement of Midwifery Student Clinical Practice - Sri Devi Syamsuddin; Ira Jayanti (Institute of Computer Science (IOCS), 2021)
Midwifery clinical learning is a learning process to achieve the target of midwifery care action skills in real cases, but the fact is that there is supervision of academic and field supervisors on the achievement of midwifery care targets in the form of SOAP is still lacking so many students are unable to explain the mindset of ASKEB 7 steps varney and management of the SOAP documentation because the cases raised came from fictitious patients. The research objective was to determine the validity of academic advisors and students towards the Monitoring Clinical Learning (MCL) application developed to achieve the midwifery practice target. The research design used is research and development (Research & Development). The development model used in this research is the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The research samples were material experts, IT / media experts, 15 Midwifery Study Program students and clinical practice academic supervisors. The results of the research were obtained from material experts, media experts, and mentors with the percentages respectively80%, 91.6% and 95% categories are very valid. The results of student implementation obtained a percentage of 91.3%very good category. So it can be concluded that the Android-based MCL application to achieve the target of student clinical practice and supervisory supervision with this practical process is very valid for use in midwifery clinical practice..